2020
DOI: 10.3390/aerospace7050049
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of the Design of a Piezoelectric De-Icing System for Small Rotorcraft Part 2/3: Investigation of Transient Vibration during Frequency Sweeps and Optimal Piezoelectric Actuator Excitation

Abstract: The objective of this research project is divided in four parts: (1) to design a piezoelectric actuator based de-icing system integrated to a flat plate experimental setup, develop a numerical model of the system and validate experimentally; (2) use the experimental setup to investigate actuator activation with frequency sweeps and transient vibration analysis; (3) add an ice layer to the numerical model, predict numerically stresses at ice breaking and validate experimentally; and (4) implement the concept to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…This comprehensive study allowed to develop a numerical model for a simple flat plate and a better understanding and optimization of the actuators driving strategies in preparation for the design and instrumentation of an experimental piezoelectric-based de-icing system for small rotorcraft. The experimental setup designed is used in the next phase of the project to study transient vibration and frequency sweeps [22]. The numerical model is used in the third phase of the project by adding ice layers for numerical and experimental investigation of vibration-based de-icing [23], with the final objective of developing and integrating a piezoelectric actuator de-icing system to a rotorcraft blade structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprehensive study allowed to develop a numerical model for a simple flat plate and a better understanding and optimization of the actuators driving strategies in preparation for the design and instrumentation of an experimental piezoelectric-based de-icing system for small rotorcraft. The experimental setup designed is used in the next phase of the project to study transient vibration and frequency sweeps [22]. The numerical model is used in the third phase of the project by adding ice layers for numerical and experimental investigation of vibration-based de-icing [23], with the final objective of developing and integrating a piezoelectric actuator de-icing system to a rotorcraft blade structure.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental tests were performed under the piezoelectric actuators excitation using sinusoidal signals at fixed frequencies to obtain steady-state mode deployment to compare with the numerical analysis results. The experimental results, given by the laser vibrometer software, present the upwards displacements in different shades of red, with lighter shades for higher magnitudes, and downwards displacements in different shades of green, also with lighter shades for higher magnitudes (see Figures 16,17,19,and 22). The operating voltage of the piezoelectric actuator was set to 200 Vpp, both experimentally and in the numerical model.…”
Section: Numerical Model Validationmentioning
confidence: 99%
“…To study the initiation or propagation of ice fractures, it is necessary to have an approximate value of the cohesive tensile strength of the ice, of the adhesive shear strength of the ice with the substrate, and of the critical strain energy release rate. Although many experiments have been carried out to measure these values, there is a relatively wide range of ice strengths, and it is not easy to select a single value because ice strength depends on many factors: temperature [27][28][29], nature and roughness of the substrate [25], strain and strain rate [29,30], ice grain size [29], and flow speed [31]. Based on several articles [28,[32][33][34][35], the range of the ice tensile strength for fresh water is from [0.6-3] MPa, and the range of the ice adhesive shear strength for fresh water is from [0.2-1] MPa.…”
Section: Methodsmentioning
confidence: 99%
“…2). The ceramics were placed next to antinodes to get a high electromechanical coupling for these specific modes [25]. Another option would have been to place the ceramics in the middle of the sample where the stresses are also important.…”
Section: Ice Substratementioning
confidence: 99%
“…The present study represents an incremental improvement and complexification of previously presented experimental and Finite-Elements Analysis (FEA)-based numerical investigations where the principle of the proposed design method was demonstrated using a simple flat plate structure. The results of these experiments were published in [17][18][19], where a comprehensive literature study was presented, and the optimal integration and excitation of the actuators, the steady-state and transient vibration response and the stresses involved in icebreaking were extensively studied experimentally and numerically. In this new study, the developed and demonstrated concept was applied to a more complex structure, e.g., a rotating small-scale 22.9 cm (9 inches) long blade setup.…”
Section: Introductionmentioning
confidence: 99%